Les enjeux du court métrage malgache - Karine Blanchon (Mise au Point)
The production of short films is very important on the African continent, especially in Madagascar. Do these short films let appear specificities? How does this format fit into the economy of the cinema in Madagascar? This article analyzes the situation of the Malagasy short films and the situation of the cinema on this island of Indian Ocean where cinema rooms have almost disappeared.